The sticky floor phenomenom a literature review - Ayu Puspitasari; Miranti Putry (Institute of Computer Science (IOCS), 2023)
The involvement of women in the world of work continues to increase every year. However, women who occupy top management positions are still very limited. This condition may be caused by the sticky floor phenomenon – the initial obstacle that hinders women's career advancement before women's careers in the glass ceiling phenomenon. This study presents the antecedents of the sticky floor phenomenon in both for-profit and non-profit organizations. An extensive literature review was carried out to get a conclusion about the factors that hinder women's career advancement. The managerial implications and opportunities for further research are discussed.